Povezani v znanju ustvarjamo prihodnost (University of Maribor Press, 2025)
Connected in Knowledge, We Create the Future. The publication “Connected in Knowledge, We Create the Future” presents the University of Maribor as a modern, interconnected, and forward-thinking academic environment that strives to become a globally recognized innovation ecosystem, where students and staff create with joy. It features all faculties, which, through their innovative study programs, contemporary teaching methods, and strong links with industry, contribute to groundbreaking research and professional achievements. The publication also highlights the academic and professional activities of the university’s members across various fields of science, art, and technology, emphasizing their contribution to societal development. It showcases distinguished alumni who have left a mark in science, culture, business, and sports, as well as the university’s initiatives promoting sustainability and social responsibility. In addition to the faculties, the University of Maribor Student Dormitories and the University Library Maribor (UKM) are presented as key pillars of the university’s study and research environment. Beginning with the 2025/2026 academic year, the Dr. Adolf Drolc Health Centre Maribor and the University Medical Centre Maribor joined the university as associated members, further strengthening the integration of education, science, and professional practice.